Charles S. Peirce e a teoria da Complexidade: algumas afinidades com o pensamento de Edgar Morin - Pizzolato, Pedro Sitta (2024)
The scientific revolutions that deeply and swiftly affected humanity from the 20th century onwards demand a Theory of Knowledge more suitable for the complex character that nature increasingly presents to us and the complex challenges humanity faces. Moreover, there is a need to adopt a reflective stance towards knowledge, critically addressing our encroaching overspecialization and mutilating oversimplification – a reconnection of Science and Philosophy towards the significant questions of humanity on its universal journey, essentially cognitive. This paper will present the historiography of the evolution of this problem in the 20th century and propose the hypothesis of adopting Charles S. Peirce's Philosophy, with its essentially cognitive and evolutionary character, counting on its Logical, Ontological, and Metaphysical framework for a Theory of Knowledge equipped with both advanced and updated paradigms and methodological tools. To achieve this, the central principles of Complexity Theory, as developed by Edgar Morin, will be explored to articulate reflections and fruitful provocations for the hypothetically possible epistemological innovation. Finally, points of possible articulation will be listed, along with academic directions in the development and testing of the proposed hypothesis